An ethnobotany of Kakheti and Kvemo Kartli, Sakartvelo (Republic of Georgia), Caucasus - Bussmann, Rainer W; Paniagua Zambrana, Narel Y; Sikharulidze, Shalva; Kikvidze, Zaal; Kikodze, David; Tchelidze, David; Khutsishvili, Manana; Batsatsashvili, Ketevan; Hart, Robbie E (Ethnobotany Research and Applications, 2020)
Background: Kahketi and Kvemo Kartli are historical provinces of Georgia located on the south-facing macro-slope of the eastern part of the Greater Caucasus (Kahketi) and east of the Lesser Caucasus (Kvemo Kartli). In this study we documented traditional plant use in Kakheti and Kvemo Kartli. Methods: Fieldwork was conducted in August-November 2018. Interviews using semi-structured questionnaires were conducted with 40 participants (26 women and 14 men), with oral prior informed consent. Results: We encountered 215 plant species belonging to 157 genera of 114 vascular plant families, and 3 fungal species and 5 undetermined fungi of at least 5 genera, belonging to at least 3 fungal families being used in the research region. Of these 114 vascular species were exclusively wild collected, 88 were grown in homegardens, and 18 were both grown in gardens and collected in the wild. Plants and their uses mostly overlapped among the areas within the region, with a slightly wider divergence in uses than in plants. The environmental fit analysis showed that a large degree of this variation was explained by differences among participant communities. The elevation of the participant community significantly fit the ordination in plant-space and explained a large degree of the variation in plant species reported but not in use-space. Gender was not significant in plant-space but was important in use space. Conclusions: The lack of forest plant use, and both forest and garden plant-use knowledge in Kakheti and Kvemo-Kartli might be traced to the fact that both regions are close to large markets in the region, which make it less necessary to grow or forage many species. In addition, Kahketi is easily one of the most fertile regions in Georgia, with a very short winter and there is essentially no need for foraging wild species e.g. for Phkhali. Lagodekhi, with its almost subtropical climate, is an extreme example of that, with almost no recorded forest plant use. Key words: Caucasus, ethnobotany, plant use, traditional knowledge, post-soviet development